Environmentally Friendly Paving Block Based on Wood Waste: The Effect of Rubber Wood Waste Content on the Physical-Mechanical Properties of Paving Block - Fauzi, Daffa Naufalian; Saputra, Bagus; Riniarti, Melya; Duryat, Duryat; Suri, Intan Fajar; Hidayat, Wahyu (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2024)
The wood sawing industry generates significant waste, consisting of wood chips, wood scraps, and sawdust. This research aims to evaluate the effect of rubber wood sawdust addition on the moisture content, water absorption capacity, and compressive strength of paving blocks. The study was conducted in August–September 2023, starting with preparing raw materials, composition planning, and test specimen fabrication. The parameters in this study included density testing, moisture content, water absorption capacity, and compressive strength. The density test results for treatments P0 were 1.11 g/cm3, P1 1.09 g/cm3, P2 1.07 g/cm3, P3 1.08 g/cm3, and P4 1.09 g/cm3. The moisture content test yielded values of 11.38% for P0, 12.56% for P1, 12.94% for P2, 13.24% for P3, and 13.80% for P4. The water absorption capacity values obtained were, for P0, 5.17%; P1, 5.40%; P2, 6.36%; P3, 8.11%; and P4, 9.27%. Compressive strength tests produced values for P0 at 7.19 N/mm2, P1 at 5.67 N/mm2, P2 at 4.22 N/mm2, P3 at 3.48 N/mm2, and P4 at 3.07 N/mm2. The addition of rubber wood sawdust to paving blocks significantly influences density, moisture content, water absorption capacity, and compressive strength values. Keywords: Composition, Compressive strength, Paving block, Sawdust waste.